Reorganisation of public administration in Greece; a report - Langrod, Georges; Organisation for Economic Co-operation and Development ([Paris] Organization for Economic Co-operation and Development, 1965)
The report was drafted by the OECD consultant at the request of the OECD, and is intended to establish some basic facts concerning administrative reform in Greece, and particularly concerning the partial reorganisation of the Civil Service
oif 20/07/16
Loans
Keywords: Civil service; Greece; Greece